STRENGTHENING EARLY CHILDHOOD EDUCATION THROUGH ENVIRONMENTAL CARE AND UTILIZATION OF SCHOOL TOYS IN GREEN SCHOOL PROGRAMS - Nabila, Dinda Fatma; Putri, Widya; Wulandari, Retno; Ismandela, Afriyane; Azizah, Azizah; Safna, Aisyah; Warmansyah, Jhoni; Sari, Meliana; Yuningsih, Restu (Fakultas Sains dan Teknologi, 2024)
This community service was conducted through the Participatory Action Research (PAR) approach to enhance the quality of early childhood education at TK Islam Harapan Ibu. Through active involvement from the school, parents, and community, this community service program aims to identify, plan, implement, and evaluate activities focused on the movement to care for the school's toy scope and integrate the Green School program. In this study, a significant improvement in children's engagement and creativity during learning activities using toys was found. Strong support from educators and parents played a crucial role in the success of this program. The sustainability of the movement to care for the school's toy scope and integration of the Green School program are expected to continue to develop and make a significant contribution to improving the quality of early childhood education in the community. Keywords: Environmental Care, School Toys, Green School Programs, Early Childhood